Elementary students’ voices: Project-based learning via Wayang media in speaking skills - Rini Sukarti; Reva Maria Valianti; Liza Murniviyanti; Arizona; Subira Kaserero; M. Khoirudin Jalil (Universitas Ahmad Dahlan, 2026)
This study addresses the critical challenge of low speaking skills among elementary school students, particularly in articulating the intrinsic elements of a story. Traditional, teacher-centered methods and a lack of innovative cultural media leave students passive and unconfident. To bridge this gap, this study examines the implementation of the Project-Based Learning (PjBL) model integrated with traditional wayang puppets. Utilizing a descriptive qualitative approach, this research investigated 30 sixth-grade students at SDN 184 Palembang, a public elementary school in Palembang, South Sumatra, Indonesia, through purposive sampling. Data were gathered via semi-structured interviews, classroom observations, and documentation, and analyzed through the interactive qualitative framework of Miles, Huberman, and Saldaña. The qualitative results indicate that the integration of PjBL and wayang puppets significantly transforms the classroom dynamic by shifting students from passive listeners to active storytellers. Students demonstrated substantial growth in speaking fluency, narrative coherence, and structural clarity when explaining story elements like characters, plots, and moral values. Furthermore, the hands-on project creation process fostered deep emotional engagement, decreased performance anxiety, and enhanced conceptual understanding. The findings imply that integrating culturally responsive PjBL with traditional wayang puppets can provide an effective student-centered approach for strengthening elementary students’ speaking skills, narrative understanding, and confidence in primary language education.